Medical disaster response: A critical analysis of the 2010 Haiti earthquake - Arnaouti, Matthew Keith Charalambos; Cahill, Gabrielle; Baird, Michael David; Mangurat, Laëlle; Harris, Rachel; Edme, Louidort Pierre Philippe; Joseph, Michelle Nyah; Worlton, Tamara; Augustin, Sylvio; , The Haiti Disaster Response – Junior Research Collaborative (HDR-JRC) (Frontiers in Public Health, 2022)
Introduction On January 12, 2010, a 7.0 magnitude earthquake struck the Republic of Haiti. The human cost was enormous—an estimated 316,000 people were killed, and a further 300,000 were injured. The scope of the disaster was matched by the scope of the response, which remains the largest multinational humanitarian response to date. An extensive scoping review of the relevant literature was undertaken, to identify studies that discussed the civilian and military disaster relief efforts. The aim was to highlight the key-lessons learned, that can be applied to future disaster response practise. Methods Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews guidance was followed. Seven scientific databases were searched, using consistent search terms—followed by an analysis of the existent Haitian literature. This process was supplemented by reviewing available grey literature. A total of 2,671 articles were reviewed, 106 of which were included in the study. In-depth analysis was structured, by aligning data to 12 key-domains, whilst also considering cross-sector interaction (Civilian-Civilian, Military-Military, and Civilian-Military). Dominant themes and lessons learned were identified and recorded in an online spreadsheet by an international research team. This study focuses on explicitly analysing the medical aspects of the humanitarian response. Results An unpreceded collaborative effort between non-governmental organisations, international militaries, and local stakeholders, led to a substantial number of disaster victims receiving life and limb-saving care. However, the response was not faultless. Relief efforts were complicated by large influxes of inexperienced actors, inadequate preliminary needs assessments, a lack of pre-existing policy regarding conduct and inter-agency collaboration, and limited consideration of post-disaster redevelopment during initial planning. Furthermore, one critical theme that bridged all aspects of the disaster response, was the failure of the international community to ensure Haitian involvement. Conclusions No modern disaster has yet been as devastating as the 2010 Haiti earthquake. Given the ongoing climate crisis, as well as the risks posed by armed conflict—this will not remain the case indefinitely. This systematic analysis of the combined civilian and military disaster response, offers vital evidence for informing future medical relief efforts—and provides considerable opportunity to advance knowledge pertaining to disaster response.